MAKING ETHICAL DECISIONS: SEEING TWITTER BOTS AS (NON) ‘HUMAN SUBJECTS’ WHEN INCLUDING THEM AS RESEARCH PARTICIPANTS - Beck, Estee; Hutchinson, Leslie (AoIR Selected Papers of Internet Research, 2015)
This collaborative talk challenges the definitions of the situated site of human subjects protection in Internet research. The collaborators address a major tension to the deliberative process of ethical decision-making as proposed in the 2012 AoIR report: the role non-human language objects (computer code and bots) have as entities worth ethical consideration in the research process about consent and risk/harm. Using the @horse_ebooks hoax as a relatively similar manipulation to that of the Facebook emotional contagion story, the speakers will talk theorize the relationship between human, algorithm, and emotional persuasion, and present findings from two wholly algorithmic Twitter bots, @sargoth_ebooks and @randi_ebooks to challenge an ontological relationship with humans and algorithms. The speakers will close with specific ethical questions related to computer code and bots and ask for audience member participation to establish future guidelines in this area. Accessible print handouts / accessible information will be provided on a website during (and made available) after the talk.